Language Assessment Purposes Most ‎Frequently Used Among Arabic Language ‎Teachers in Jordan - Bani Yassin, Rasha; Al-Khawaldeh, Mohammed (Jordan Journal of Educational Sciences, 2023)
The study aimed at revealing the most frequently used language assessment purposes used among Arabic language teachers in Jordan and whether this differs according to their qualifications and years of experience. To achieve the aims of the study, a 24- items language assessment purpose scale was , distributed into three domains: assessment of learning, assessment for the purpose of learning, and the assessment as learning itself. The sample of the study consisted of 205 Arabic teachers in the schools affiliated with the Bani Kenana district in Irbid governorate, selected by the accessible method. The results of the study showed that the assessment of learning was the most frequently used by Arabic language teachers, Following this came the assessment for the purpose of learning, and finally the assessment as learning itself. The results also showed that there were no statistically significant differences in their rates of language assessment purposes most frequently used due to their qualifications and years of experience. In light of these results, the study recommends holding training courses for Arabic language teachers in assessment for learning and assessment as learning.